Seeing The World Through Rose-colored Glasses? Neglect of Consensus Information in Young Children's Personality Judgments - Boseovski, Janet J. (2008)
The present study examined the use of consensus information in early childhood. Ninety-six three- to six-year-olds watched a demonstration that depicted the positive or negative behavior of one or several actors toward a recipient (low vs. high consensus, respectively). Subsequently, participants made behavioral predictions and personality judgments about the actors and recipients. Participants viewed all story characters favorably and were reluctant to assign blame for negative outcomes, although the appropriate use of consensus information increased with age for behavioral predictions. These findings suggest that there is a positivity bias in young children's personality judgments even in the face of explicit contradictory behavioral evidence. Children's early `theory of personality' is apparently driven by a baseline assumption that people are nice.